Antitumor activity of gamma-irradiated Rosa canina L. against lung carcinoma in rat model: a proposed mechanism - Omayma A. R. Abo-Zaid; Fatma S. M. Moawed; Eman S. Eldin; Mostafa A. Farrag; Esraa S. A. Ahmed (BMC Complementary Medicine and Therapies)
Abstract Background Lung cancer is one of the most prevalent malignancies globally and is the leading cause of cancer-related mortality. Although cisplatin is a widely utilized chemotherapeutic agent, its clinical efficacy is often hampered by significant toxicity and undesirable side effects. Rosa canina, a medicinal plant, has demonstrated a range of beneficial biological activities, including anti-inflammatory, anticancer, immunomodulatory, antioxidant, and genoprotective effects. Methods This study aimed to investigate the potential of Rosa canina to enhance the anticancer efficacy of cisplatin in a dimethyl benz(a)anthracene-induced lung cancer model using female rats. The animals were administered Rosa canina, cisplatin, or a combination of both treatments. The expression levels of critical signaling molecules were evaluated, including phosphoinositide-3-kinase (PI3K), Akt, mammalian target of rapamycin (mTOR), cleaved poly (ADP-ribose) polymerase (PARP-1), myeloid differentiation factor 88 (MyD88), and tumor necrosis factor receptor-associated factor (TRAF), in addition to various autophagic markers. Furthermore, we assessed the levels of toll-like receptor 2 (TLR2), nuclear factor kappa B (NF-κB), and apoptotic markers in lung tissue, complemented by histopathological examinations. Results The combined treatment of Rosa canina extract and cisplatin significantly inhibited lung cancer cell proliferation by downregulating PARP-1 and the TLR2/MyD88/TRAF6/NF-κB signaling pathway, as well as the PI3K/Akt/mTOR pathway. Moreover, this combination therapy promoted autophagy and apoptosis, evidenced by elevated levels of autophagic and apoptotic markers. Conclusion Overall, the findings of this study suggest that Rosa canina enhances the anticancer effects of cisplatin by inhibiting cancer cell proliferation while simultaneously inducing autophagy and apoptosis. Thus, Rosa can be used as adjuvant to cisplatin chemotherapy to overcome its limitations which may be considered a new approach during lung cancer treatment strategy. Graphical Abstract